Interruptions in the agricultural production system and food value chain in the times Covid-19 pandemic - Johan, Prisca Divra; Ahmed, Osumanu Haruna; Musah, Adiza Alhassan; Salleh, Nur Thaqifah Salihah; Jamaludin, Mohd Hafiz; Abdullah, Rose; Anwari, Anisah Syakirah; Zainuddin, Zarina (Springer, 2025)
The agrarian sectors such as agriculture, fisheries, and livestock which are vital aspects of food systems have not been spared by COVID-19. The agri- cultural sector forms the backbone of the global economy as it provides livelihood to the developed and developing countries. Therefore, disruptions in food security and the agricultural sector is having and may continue to have far-reaching impacts on the agricultural ecosystem services. As a result, the pandemic has demonstrated the fragility of agriculture and the related food chain. Owing to the importance of the agrarian sectors, this review paper highlights the interruptions in the food and agri- culture industry as a result of the on-going COVID-19 pandemic. The current state of the agriculture ecosystem in relation to the COVID-19 has indicated the importance of sustainable and resilient food system approaches to ensure future food security and food provision.